1999
DOI: 10.1017/s0033291799001221
|View full text |Cite
|
Sign up to set email alerts
|

Can children with autistic spectrum disorders perceive affect in music? An experimental investigation

Abstract: In contrast to their performance within social and interpersonal domains, children with autistic disorders showed no deficits in processing affect in musical stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 27 publications
7
100
1
3
Order By: Relevance
“…Researchers have reported that children with ASD who have affective and interpersonal deficits can perceive affect in music (Heaton, Hermelin & Pring, 1999).…”
Section: Perception Of Music In Children With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have reported that children with ASD who have affective and interpersonal deficits can perceive affect in music (Heaton, Hermelin & Pring, 1999).…”
Section: Perception Of Music In Children With Asdmentioning
confidence: 99%
“…Musical stimuli are commonly organized and perceived by patterns, and this musical pattern perception is observed in children with ASD (Heaton, Hermelin & Pring, 1999;Orr, Myles & Carlson, 1999). Pattern perception is also the primary mechanism for speech and language in children with ASD (Prizant, 1983).…”
Section: Perception Of Music In Children With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the design paradigms was to strive for agency (Happé, 1999;Frith & Happé, 1999;Heaton, 1999): putting the children "in charge" of an environment that was at once rich with sensory offerings and devoid of any social context or symbolic content. Another important design paradigm was the cross-modal, or 'synaesthetic' aspect (Williams, Gumtau, & Mackness, 2012).…”
Section: Mediatementioning
confidence: 99%
“…As discussed by Khetrapal, the article by Khalfa, Roy, Rainville, Dalla Bella & Peretz (2008) showed that happy-sad distinctions in music are mainly dependent on pitch cues, so studying pitch was the most reasonable place to begin the exploration of musical emotion perception in ASD. These studies have shown that children with autism can match the emotion conveyed by a piece of music to a schematic happy or sad face (Heaton, Hermelin & Pring, 1999) or to a pictorial representation of a more complex emotion, such as tenderness (Heaton, Allen, Williams, Cummins & Happé, 2008). The second study may have required perception and encoding of cues other than pitch and key to make the emotion judgments (for example, differentiating fear from anger).…”
Section: Asd and Auditory Perceptionmentioning
confidence: 99%